# Factor 6a^8-6p^8

6a8-6p8
Factor 6 out of 6a8-6p8.
Factor 6 out of 6a8.
6(a8)-6p8
Factor 6 out of -6p8.
6(a8)+6(-p8)
Factor 6 out of 6(a8)+6(-p8).
6(a8-p8)
6(a8-p8)
Rewrite a8 as (a4)2.
6((a4)2-p8)
Rewrite p8 as (p4)2.
6((a4)2-(p4)2)
Since both terms are perfect squares, factor using the difference of squares formula, a2-b2=(a+b)(a-b) where a=a4 and b=p4.
6((a4+p4)(a4-p4))
Factor.
Simplify.
Rewrite a4 as (a2)2.
6((a4+p4)((a2)2-p4))
Rewrite p4 as (p2)2.
6((a4+p4)((a2)2-(p2)2))
Since both terms are perfect squares, factor using the difference of squares formula, a2-b2=(a+b)(a-b) where a=a2 and b=p2.
6((a4+p4)((a2+p2)(a2-p2)))
Factor.
Factor.
Since both terms are perfect squares, factor using the difference of squares formula, a2-b2=(a+b)(a-b) where a=a and b=p.
6((a4+p4)((a2+p2)((a+p)(a-p))))
Remove unnecessary parentheses.
6((a4+p4)((a2+p2)(a+p)(a-p)))
6((a4+p4)((a2+p2)(a+p)(a-p)))
Remove unnecessary parentheses.
6((a4+p4)(a2+p2)(a+p)(a-p))
6((a4+p4)(a2+p2)(a+p)(a-p))
6((a4+p4)(a2+p2)(a+p)(a-p))
Remove unnecessary parentheses.
6(a4+p4)(a2+p2)(a+p)(a-p)
6(a4+p4)(a2+p2)(a+p)(a-p)
Factor 6a^8-6p^8

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top